Emotional Intelligence And Leadership Competencies: A Study Of Ministry Of Works, Owerri - A., Emerole Gideon; Charles, Nwaji; Etifit, John Okpoyo (Archives of Business Research, 2018)
The study examined Emotional Intelligence and Leadership Competencies: A Study of Ministry of Works, Owerri. In conducting the study, descriptive survey approach was adopted and data was generated from a five point likert scale questionnaire. The study covered a population of one hundred and twenty three (123) senior and junior members of staff of the ministry. Taro Yamene formula was used to select a sample of 94 respondents. Out of the 94 questionnaires distributed, 88 were correctly filled and returned; thereby given a questionnaire return rate of 93.62%. The data gathered was analyzed with the kruskawalis (H) test. The study found that Leadership competence is an integral component of organizational performance, hence, it was concluded that the emotional state of the leader has significant effect on his/her competence. The study therefore recommends that Leaders should demonstrate emotional self-control, transparency, adaptability, initiative and be optimistic. These are the inevitable high personal standards that drives them to constantly seek performance improvements, hence; enhancing their goal achievement orientation and that to develop quality social awareness, leaders should strive to exhibit conflict management skills, be inspirational, drive changes in their environment and develop others. These helps to generate an atmosphere of friendly collegiality and make them models of respect, helpfulness, and co-operation, thereby drawing others into active, enthusiastic commitment to the collective effort, and build spirit and identity.